The abs diet for women workout [videorecording (DVD)] - Smith, Jessica; Zinczenko, David (Distributed by GT Media, 2008)
Designed to maximize fat burning while minimizing workout times, and focuses on strength training to build lean muscle, cardio to burn fat and ab exercises that hit all five regions of the abdominal muscles.